Information and communication techologies and the urban transformation of South African informal settlement communities - Mitchell, Hylton (School of Architecture, Planning and Geomatics, 2015)
The paper explores the Information and Communication Technology (ICT) practices of the Social Justice Coalition (SJC), a grassroots community based organisation working with informal settlement communities in Khayelitsha, a largely informal neighbourhood on the south-eastern fringes of Cape Town, South Africa. The study focuses on SJC’s advocacy work in the delivery of ‘decent sanitation’ to informal settlement residents. This has been an explosive political issue for a number of years now. Many communities within Khayelitsha rely on communal toilets for sanitation, and the maintenance thereof has left much to be desired. Within the larger theme of digital activism, three main research areas were identified and explored: the appropriation of ICTs by the SJC’s field staff, the use of their Web 2.0 based social networking sites (SNS) in their advocacy work and digital mapping of portable communal toilets in the RR Section of Khayelitsha. The research interrogates the use of ICT as a strategic tool for knowledge-based community empowerment, with the aim of understanding how these emerging uses of technology could assist urban transformation work within this sprawling area. The research emphasizes the roles of various actors, the roles played by different technologies and the relations between technology and people. The emphasis on agency reveals that technology is not enough to augment empowerment processes. Technology-organisational relations are enmeshed within an institutional frame, where the enrollment of technology as actor, requires a repositioning of network relations, in order for it to fulfill its potential as an empowerment tool.